EFEKTIVITAS PELAKSANAAN KEBIJAKAN IJIN SAKIT BERDASARKAN PERATURAN PERUSAHAAN TAHUN 2023-2025 TERKAIT SURAT KETERANGAN DOKTER BPJS KESEHATAN PADA PT WILSON LAUTAN KARET, TBK - Herlina Saparingga; Iwan Riswandi; Adwin Tista (Yayasan Pendidikan Literasi Borneo, 2025)
Sick leave policy is a crucial component of labor rights protection and human resource management implementation within a company. However, at PT Wilson Lautan Karet, Tbk, issues have been identified in the implementation of sick leave, particularly concerning the recognition of medical certificates issued by BPJS Health facilities. This study aims to evaluate the effectiveness of the sick leave policy implementation based on the Company Regulations from 2023 to 2025, and to assess the extent to which BPJS medical certificates are acknowledged as valid documentation. The research method used is descriptive qualitative with a case study approach, involving interviews with HRD personnel and employees, as well as document analysis. The findings reveal that the implementation of the policy has not been fully effective due to the HRD’s limited understanding of national health insurance regulations and the lack of alignment between internal company policies and the BPJS system. It is concluded that the execution of sick leave policy remains suboptimal, resulting in uncertainty for employees. The study suggests a revision of company regulations to align with government policies, along with enhancing HRD's comprehension through training on occupational health regulations and the national social security system